Proteins involved in transport - Balch, William Edward (Small GTPases and their regulators, 1995)
General Description of the Volume: Small GTPases play a key role in many aspects of contemporary cell biology: control of cell growth and differentiation; regulation of cell adhesion and cell movement; the organization of the actin cytoskeleton; and the regulation of intracellular vesicular transport. This volume plus its companion Volumes 255 and 256 cover all biochemical and biological assays currently in use for analyzing the role of small GTPases in these aspects of cell biology at the molecular level. Volume 257 provides detailed protocols to effectively produce, modify, and assay for the function of small GTPases involved in vesicular traffic through the secretory pathway of eukaryotic cells. General Description of the Series: The critically acclaimed laboratory standard for more than forty years, Methods in Enzymology is one of the most highly respected publications in the field of biochemistry. Since 1955, each volume has been eagerly awaited, frequently consulted, and praised by researchers and reviewers alike. Now with more than 300 volumes (all of them still in print), the series contains much material still relevant today--truly an essential publication for researchers in all fields of life sciences. Key Features * Assays to measure GTP exchange and hydrolysis * Expression and purification of small GTPases * Posttranslational modifications of Rab proteins * Generation of trans dominant mutants * Expression and purification of Rab effector proteins